Maximizing Benefits of Space Technology for Nepalese Society - Baral, Toya Nath; Bhatta, Ganesh Prasad (Journal on Geoinformatics, Nepal, 2006)
Advancements in the space technology have contributed to the human life considerably. The technology has been exploited for making human life easier and more secure in large extent. Space technology application for managing unavoidable natural disasters, human induced disasters and other societal problems/situations is one of such examples. Space technology application has brought the possibilities of real time mapping of disasters and its on-time management. Application of space technology in Nepal was brought into practice during 1970's. However, it has been realized that institutional infrastructure is yet to be developed to exploit the technological advancement of space technology. Survey Department is the leading organisation for launching space programs in Nepal. The department is working with collaborative approach with various organization to utilize the space technology information for the development activities in Nepal so that the benefits could be maximized for the society. This paper tries to highlight on the state of the art of the space technology application in the country, the potential areas for maximizing space benefits for the society, the challenges to cope with the space technology applications and the area of regional cooperation requiredto enhance the space programs of the country .Lack ofhuman resources and necessary infrastructures are the main constraints in Nepal for launching space programs effectively. Regional Cooperation could support the country in this effort.